On the absent ground of transnational partnerships in education: A post-foundational intervention. (8th August 2019) - Knutsson, Beniamin; Lindberg, Jonas
ABSTRACT: Transnational multi-stakeholder partnerships (MSPs) are proliferating in the domain of education and development. This paper intervenes in scholarly discussions on such partnerships by pondering what post-foundational political thought might add. It is argued that both liberal and critical literature, albeit from very different viewpoints, tend to foreground order and stability. Drawing on post-foundational political theory, and a case study of the Global Partnership for Education, the present paper explores transnational MSPs in education as incomplete hegemonic projects. By bringing attention to fissures and disruptions, the paper exposes how the absent ground of 'the political' ultimately haunts the stability of partnerships.